Becoming confident teachers : a guide for academic librarians - McGuinness, Claire (Chandos information professional series., 2011)
Becoming Confident Teachers examines the teaching role of information professionals at a time of transition and change in higher education. While instruction is now generally accepted as a core library function in the 21st century, librarians often lack sufficient training in pedagogy and instructional design; consequently finding their teaching responsibilities to be stressful and challenging. By exploring the requirements and responsibilities of the role, this book guides teaching librarians to a position where they feel confident that they have acquired the basic body of knowledge and proce.